HUBUNGAN VARIABEL PENDAPATAN PETANI ALIH GUNA LAHAN SAWAH KE KARET (Studi Kasus di Desa Nusaraya Kecamatan Belitang III) KABUPATEN OKU TIMUR - Ema Pusvita; Munajat Munajat (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2021)
The purpose of this study is 1) to identify the process of land conversion to rubber plants, 2) to calculate farm income after the conversion of rice fields to rubber plants, 3) to analyze the level of closeness of the income relationship of farmers after transferring the function of paddy fields to rubber trees on factors that affect income. This study used case study method, and then the data was analyzed by using the Spearman Rank Correlation. The results showed that 1) identification of the process of changing the function of paddy fields to rubber plants is determined by the rubber price factor which is higher than the price of rice, 2) the average income of farmers who convert rice fields to rubber is higher because of the two commodities being cultivated, namely rice and rubber, 3) the factors of income and amount of rubber production, income and area of rubber land, income and expenditure of farmers, amount of rice production and area of paddy land, amount of rubber production and rubber land area, the amount of rubber production and farmer expenditure, rubber land area and farmer expenditure, age and education of farmer are highly correlated in influencing the income of the conversion of paddy fields to rubber plants.